Effect of Fresh Frozen Plasma Infusion on Hospital Length of Stay for Patients With Hereditary Angioedema - Subhan Khalid; Alan T. Hitch (Journal of Health Economics and Outcomes Research)
# Background Patients with hereditary angioedema treated with fresh frozen plasma (FFP) infusion face complications and risk of side effects.